2002
DOI: 10.2337/diacare.25.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Treatment of Diabetes With Glyburide May Both Be Risk Factors for Acute Pancreatitis

Abstract: OBJECTIVE -To evaluate risk factors, notably drugs, for acute pancreatitis.RESEARCH DESIGN AND METHODS -A population-based case-control study was conducted of 1.4 million inhabitants, aged 20 -85 years, of four regions in Sweden between 1 January 1995 and 31 May 1998. A total of 462 case subjects were hospitalized in surgery departments for their first episode of acute pancreatitis without previous gallbladder disease. A total of 1,781 control subjects were randomly selected from a population register. Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
2
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 13 publications
5
69
2
2
Order By: Relevance
“…Metformin, for example, which is frequently combined with incretin mimetics, is associated with a decreased cancer risk (Evans et al 2005), and decreased mortality in cancer patients (Gallagher & LeRoith 2011). Sulfonylurea on the other hand, might increase risk for pancreatitis (Blomgren et al 2002) and solid tumors (Currie et al 2009). …”
Section: Caveatsmentioning
confidence: 99%
“…Metformin, for example, which is frequently combined with incretin mimetics, is associated with a decreased cancer risk (Evans et al 2005), and decreased mortality in cancer patients (Gallagher & LeRoith 2011). Sulfonylurea on the other hand, might increase risk for pancreatitis (Blomgren et al 2002) and solid tumors (Currie et al 2009). …”
Section: Caveatsmentioning
confidence: 99%
“…In addition, we did not compare the HbA1c level with the number of drugs used, a potential confounding situation, since few studies have shown a lower incidence of AP with lower HbA1c level due to metformin or glyburide use. 29,30 It is interesting to note that in 70.6% cases, alcohol was not found to be the predominant etiological risk factor. The diagnosis was based on patient evaluation at the time of enrollment.…”
mentioning
confidence: 99%
“…Abdominal pain, ultrasound-confirmed pancreatic pathological changes and increased plasma amylase and lipase concentrations are the most common markers of acute pancreatitis in the clinic (21). Type 2 diabetes and/or obesity are risk factors for the development of pancreatitis, and obesity increases its severity and mortality rate (5,28,34). The cellular functions and molecular mechanisms responsible for initiating and modifying the severity of pancreatitis have not been fully elucidated.…”
mentioning
confidence: 99%